My Dog Tulip Based on a Book by J.R. Ackerley - Fierlinger, Paul; Fierlinger, Sandra; Plummer, Christopher; Redgrave, Lynn; Rossellini, Isabella (Axiom Films, 2011)
"My Dog Tulip" is an animated film about Joe Randolph Ackerley, the one time arts editor of the (now defunct) weekly BBC magazine "The Listener", and his dog. Ackerley, while certainly a man of letters, was not the most prolific of authors, having published no more than four main works in his lifetime. A significant portion of his perhaps insignificant canon takes the form of memoir, and his 1956 work "My Dog Tulip" is no exception. This particular memoir, however, might seem like the unlikely source of inspiration for a big screen animation chronicling as it does the 16 years of his life shared with a dog, his beloved Alsatian Tulip ... "My Dog Tulip" is an amusing portrait of canine life equal parts touching and vulgar. But there is more to it than just amusing gratuity. Being an openly gay man in the mid-twentieth century one can assume that Ackerley was more than familiar with the complicated nature of human relationships. What lies beneath the surface of "My Dog Tulip", then, are Ackerley's quite profound meditations on love, devotion and friendship. Who is the ideal friend? Well, as Ackerley discovers, it might as well be the four-legged one who sicks up on the carpet. And then eats it. [bestforfilm.com]